2019
DOI: 10.1073/pnas.1901795116
|View full text |Cite
|
Sign up to set email alerts
|

Leptin’s hunger-suppressing effects are mediated by the hypothalamic–pituitary–adrenocortical axis in rodents

Abstract: Leptin informs the brain about sufficiency of fuel stores. When insufficient, leptin levels fall, triggering compensatory increases in appetite. Falling leptin is first sensed by hypothalamic neurons, which then initiate adaptive responses. With regard to hunger, it is thought that leptin-sensing neurons work entirely via circuits within the central nervous system (CNS). Very unexpectedly, however, we now show this is not the case. Instead, stimulation of hunger requires an intervening endocrine step, namely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 108 publications
2
53
0
Order By: Relevance
“…Similarly, ob/ob mice, which lack the ability to secrete leptin, showed no catecholamine or temperature response to refeeding, but both increased in response to injection with recombinant leptin, again directly implicating leptin in postprandial increases in body temperature (Figure 3, B-D). However, blocking leptin action with a small molecule antagonist reversed the feeding-induced increases in catecholamines and body temperature while increasing food intake and preventing the reversal of hypercorticosteronemia with refeeding (Figure 3, F-H) (54). Taken together, these data indicate that an increase in plasma leptin concentration is both necessary and sufficient to cause increases in body temperature under postprandial conditions and of leptin on the hypothalamus-adrenal medulla-adipose tissue axis in mediating this effect.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, ob/ob mice, which lack the ability to secrete leptin, showed no catecholamine or temperature response to refeeding, but both increased in response to injection with recombinant leptin, again directly implicating leptin in postprandial increases in body temperature (Figure 3, B-D). However, blocking leptin action with a small molecule antagonist reversed the feeding-induced increases in catecholamines and body temperature while increasing food intake and preventing the reversal of hypercorticosteronemia with refeeding (Figure 3, F-H) (54). Taken together, these data indicate that an increase in plasma leptin concentration is both necessary and sufficient to cause increases in body temperature under postprandial conditions and of leptin on the hypothalamus-adrenal medulla-adipose tissue axis in mediating this effect.…”
Section: Resultsmentioning
confidence: 76%
“…22 However, studies in humans and experimental animals suggest that supra-physiological levels of glucocorticoids cause hyperphagia and obesity perhaps by reducing sensitivity to leptin. 21,23,24 Leptin acts via the leptin receptor (OBRb) expressed in hypothalamic nuclei. Based on studies in vitro in a human hepatoma cell line and in vivo in rats, it has been shown that formation of leptin-OBRb complex leads to activation of tyrosine phosphorylation through JAK/STAT pathway.…”
Section: Glucocorticoid-induced Hyperphagia and Disposition Of Nutrientsmentioning
confidence: 99%
“…The fact that Zbtb16 expression is induced by GC signaling bears significant implications in Zbtb16's involvement in energy homeostasis. In addition to their function in the periphery, GCs centrally control feeding behavior, energy expenditure, and autonomic output to peripheral organs (Zakrzewska et al, 1999;Cusin et al, 2001;Kellendonk et al, 2002;Bernal-Mizrachi et al, 2007;Veyrat-Durebex et al, 2012;Yi et al, 2012;Laryea et al, 2013;Solomon et al, 2015;Perry et al, 2019). More importantly, GCs are required for the development of both genetic and dietinduced obesity and interact with leptin signaling (Yukimura and Bray, 1978;Saito and Bray, 1984;Bray et al, 1992;Makimura et al, 2000;Perry et al, 2019).…”
Section: Discussionmentioning
confidence: 99%